Arachidonic acid and store-independent Ca2+ entry - Munaron, Luca (Henry Stewart Talks, 2007)
Agonist-activated calcium entry: different modes, Synthesis and metabolism of arachidonic acid (AA), Properties of AA-activated calcium channels, Other effects of AA on calcium homeostasis, Calcium entry and cell proliferation, AA as a critical mediator of mitogen-activated calcium entry in fibroblasts, Role of AA-dependent calcium entry in endothelial cell proliferation and angiogenesis, Nitric oxide, calcium entry and angiogenesis, Regulation of proangiogenic calcium signals: a complex picture
Updated at 2011/08/16